Uterine sarcoma with ambiguous histomorphology: A case report - Eirwen M. Miller; Yumei Fu; Ruben Barrera Vera; Gary L. Goldberg; Rouzan G. Karabakhtsian (Elsevier, 2017)
Background: Leiomyosarcomas (LMS) and endometrial stromal sarcomas (ESS) may display overlapping histomorphology, which may challenge diagnostic accuracy. Since LMS and ESS have vastly different clinical behavior and adjuvant therapy recommendations, accurate diagnosis is critical. Case: We present the case of an 83-year-old female with postmenopausal bleeding who underwent total abdominal hysterectomy with bilateral salpingo-oophorectomy for clinically atypical appearing leiomyomata. Histologically, dual populations of cells with morphologic features of low-grade ESS and high-grade spindle cell sarcoma were seen. Immunohistochemistry and molecular studies revealed the cells to be of smooth muscle derivation, rendering a diagnosis of high-grade LMS with heterogeneous morphology (stage IB). The patient received adjuvant gemcitabine plus docetaxel. She recurred 8 months after completion of chemotherapy and was transferred to hospice care. Conclusion: Ancillary studies, such as immunohistochemistry and molecular testing, aid in accurate subcategorization of uterine sarcomas with ambiguous histomorphology.